Growth performance and intestinal histomorphology of Nile tilapia juveniles fed probiotics - doi: 10.4025/actascianimsci.v35i4.18610 - Nakandakare, Ivan Bernardoni; Iwashita, Marina Keiko Pieroni; Dias, Danielle de Carla; Tachibana, Leonardo; Ranzani-Paiva, Maria José Tavares; Romagosa, Elizabeth (Acta Scientiarum. Animal Sciences, 2013)
The objective of this study was to assess the growth performance and the histomorphometric characterization of the middle intestine of GIFT strain Nile tilapia, Oreochromis niloticus juveniles fed probiotics, added either before or after the feed processing. The experimental design was completely randomized, with five treatments and five replications: pelleted feed without any probiotic; pelleted feed with inclusion of probiotic before the processing; pelleted feed with inclusion of probiotic after the processing; extruded feed without any probiotic and extruded feed with inclusion of probiotic after the processing. Two hundred and fifty juveniles were distributed in 25 aquaria (20L) and fed for 63 days. Differences in the mean values of total weight were found at the end of the experiment. After 42 days of feed intake, significant differences in feed conversion were verified for treatments with extruded diets when compared to the pelleted ones. The fishes fed diets supplemented with probiotic presented increase in the thickness of the epithelium of the intestine. The best zootechnical performance was observed in the extruded diet supplemented with probiotic added after the feed processing. The inclusion of 4.0 x 108 CFU g-1 of Bacillus subtilis and 4.0 x 108 CFU g-1 of Bacillus toyoi in both the pelleted and the extruded diets promoted an increase in the thickness of the epithelial layer of the middle intestine.